Mild Nitric Acid Treatments to Produce Nitrocellulose from Kapok Fiber (Ceiba Pentandra) - Fitriannoor Fitriannoor; Hesti Wijayanti; Rinna Juwita; Iryanti Fatyasari Nata (Jurnal Bahan Alam Terbarukan, 2023)
Kapok (Ceiba pentandra) is one of the natural fibrous sources with a high content of cellulose. The natural kapok used contains 54.3% of cellulose, 11.3% of hemicellulose, and 19.11% of lignin. Kapok is a potential material to be explored by isolating the fiber, then converting into nitrocellulose. The effect of nitric acid concentration on the nitration process and characterization of material were investigated. Kapok fiber was isolated by delignification and bleaching process. Delignification was done in the presence of 5% (w/v) of NaOH and 30% (v/v) of H2O2 for alkaline and acid hydrothermal treatment, respectively. Kapok was washed until neutral pH and dried in an oven at 100 oC for 4 h to get kapok fiber (CK). For the nitration process, CK 5% (w/w) was added to a solution of 15% (v/v) phosphoric acid and variation of 15%, 20%, and 25% of nitric acid. The mixture was stirred at 10 oC, 300 rpm, for 30 min. The solid CK was separated and poured into hot water for 5 min and continuously washed with demineralized (DI) water and sodium hydrogen carbonate until neutral pH. The nitrocellulose (KN) was produced after the material dried. The smooth surface of fiber and diameter around 14.5-19.1 Âµm was changed into a plat fiber of 13.3-21.2 Âµm after hydrothermal treatment. The crystallinity index (CrI) of CK was increased up to 58.17% based on X-Ray Diffraction (XRD) observation. The degree of substitution (DS) was calculated by data spectra of Fourier Transform-Infra Red (FT-IR) analysis of a specific functional group for N-O and C-O stretching vibrations. The DS optimum value was achieved at about 0.885 at concentration of 20% nitric acid (NK20). The synthesis of nitrocellulose kapok fiber-based has potential as a functional material.